Using Evidence and Coalitions to Scale-Up a National Early Education Initiative: The Case of Law 248/2015 in Romania - Gheorghiu, Maria; Hawke, Leslie; de Laat, Joost; Papari, Cǎtǎlina-Alexandra (Frontiers in Public Health, 2021)
In 2015, Romania took an important step towards increasing disadvantaged children’s participation in early education programmes through the passage of legislation creating a nationwide conditional cash transfer programme linked to preschool attendance. The programme was modelled on the incentive component of a 5-year pilot project ”Every Child in Preschool” (“FCG”) initiated by Asociatia OvidiuRo (“OvR”), a small non-governmental organisation. This paper explores how OvR used evidence from its pilot, global research, a quasi-experimental evaluation, collaboration with local authorities, and an intensive advocacy effort toward the legislative and executive branches of the national government to achieve the national scale-up of an early education initiative designed to create equal access in kindergarten among Roma and other impoverished, marginalized children.